401 Myocardial viability and ischaemia assessment in chronic coronary total occlusions according to collaterals distribution: a retrospective analysis. (8th December 2021) - Pinto, Giuseppe; Chiarito, Mauro; Liccardo, Gaetano; Baggio, Sara; Bacci, Elodi; Gasparini, Gabriele; Francone, Marco; Stefanini, Giulio; Condorelli, Gianluigi; Monti, Lorenzo
Abstract: Aims: Whether CTO-PCI (chronic total occlusions—percutaneous coronary intervention) offers clinical benefit over optimal medical therapy is still a matter of debate. Viability and ischaemia assessment could improve selection of candidates to PCI. Traditionally, well-developed collaterals are considered a marker of myocardial viability in CTO territory. Current literature offers few data concerning the relationship between viability/ischaemia and collaterals distribution. Methods and results: We retrospectively analysed the Cardiovascular Magnetic Resonance (CMR) studies and coronary angiographies of patients with at least one CTO referred at Humanitas Research Hospital between June 2009 and September 2020. We included 131 patients who underwent CMR with LGE assessment; of them, 111 (85%) underwent stress-CMR with adenosine. AHA segments (16 segment/patient for a total of 2096 segment assessed) were assessed on three short axis projection and scored for WMSI on cine images, for the presence of ischaemia on first pass perfusion, and for viability on LGE images. Viability was defined as LGE transmurality ≤50% and WMSI (wall motion score index) >1. Patients were divided in three groups according to collaterals distribution at coronary angiography: totally developed collaterals (TD) if they had both Rentrop 3 grade and Werner 2 grade collaterals (21 patients); well-developed collaterals (WD) if they had Rentrop 3 or Werner 2 grade collaterals (29 patients); poorly developed collaterals (PD) if they had neither Rentrop 3 or Werner 2 grade collaterals (81 patients). Patients with TD collaterals were more likely to have viable segments in the CTO-territory (90% of the segments in TD, 76% in WD, and 71% in PD, coeff. 0.107, P < 0.001). No statistically significant differences were found between groups as regard the amount of ischaemic segments (61% of the segments in TD, 65% in WD, and 60% in PD, P = 0.189). Conclusions: The presence of myocardial viability is slightly associated with the degree of coronary collateralization at coronary angiography while the amount of ischaemia is not. Stress CMR should be considered in CTO patients before a reopening attempt.